A Muslim Theologian in the Sectarian Milieu : ʿAbd al-Jabbār and the Critique of Christian Origins - Reynolds, Gabriel (Brill Book Archive Part 1, ISBN: 9789004472495., 2004)
In 385 AH/AD 995 the Qāḍī 'Abd al-Jabbār, well known for his Mu'tazilī theological writings, wrote the Confirmation of the Proofs of Prophecy , a work that includes a creative polemic against Christianity. 'Abd al-Jabbār reinterprets the Bible, Church history (especially the lives of Paul and Constantine) and Christian practice to argue that Christians changed the Islamic religion of Jesus. The present work begins with an examination of the controversial theory that this polemic was borrowed from an unkown Judaeo-Christian group. The author argues that 'Abd al-Jabbār's polemic is better understood as a response to his particular milieu and the on-going inter-religious debates of the medieval Islamic world. By examining the life and thought of 'Abd al-Jabbār, along with the Islamic, Christian and Jewish antecedants to his polemic, the author uncovers the intimate relationship between sectarian controversy and the development of an Islamic doctrine on Christianity.